The Relationship Between Sports and Stress Levels in Medical Students of The Class of 2022 - Batubara, Frisca Ronauli; Anandinata, I Nyoman Dieva; Achmad, Luana N. (Jurnal KESANS : Kesehatan dan Sains, 2025)
Sports is all kinds of physical activity in the form of games and competitions against oneself, others, or natural elements. Sports play a crucial role in maintaining both physical and mental health of individuals. Lack of sports can increase stress levels, negatively impacting an individual’s well-being. This research aims to explore the relationship between sports and stress levels among students of the Faculty of Medicine, Christian University of Indonesia (FK UKI) class of 2022. Through an analytical survey approach with a cross-sectional method, data were obtained from the Godin leisure-time exercise questionnaire and the PSS-10 questionnaire filled out by 116 respondents. The sample was taken based on a population of 164 students. The analysis results indicate a significant relationship between sports and stress levels among FK UKI class of 2022 students (p < 0.001; correlation coefficient -0.435). Most respondents were 19 years old and predominantly female. This study concludes that sports play a role in reducing stress levels among these students. The implications of this research reinforce the importance of integrating sports into mental health approaches in educational environments as effective interventions in addressing student stress. Thus, integrating sports into students' daily activities can positively contribute to improving their physical and mental well-being and strengthening the relationship between sports and mental health.